Optimalisasi Manajemen Peserta Didik dalam Meningkatkan Mutu Pendidikan di Sekolah Berbasis Pesantren - Mustajib; Sholhah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research discusses student management to improve the quality of students at SMA Darul The Islamic Boarding School Mojokerto. The purpose of this study is to find out: 1) How the implementation of student management at SMA Darul Qur'an The Islamic Boarding School Mojokerto can contribute to improving the quality of students; and 2) What factors affect the success of the implementation of student management in improving the quality of students in schools. This study uses a qualitative descriptive method with a case study approach. The data sources used are primary data and secondary data. Data collection methods include observation, interviews, and documentation. The results of the study show that: 1) The application of student management is very important to improve the quality of students because good management, schools can more easily achieve this quality improvement. 2) Factors that affect the success of the implementation of student management include a holistic and inclusive school approach supported by Islamic values, strong and visionary leadership, continuous support from leaders in the implementation of student management, active participation of students in decision-making, quality, and development of teacher staff, and close partnerships with parents.